2018
DOI: 10.1111/dom.13174
|View full text |Cite
|
Sign up to set email alerts
|

Overtreatment of older patients with type 2 diabetes mellitus in primary care

Abstract: Given that there are indications of overtreatment in older patients with type 2 diabetes in both the United States and Europe, we assessed the level of personalized diabetes treatment for older patients in primary care, focusing on overtreatment. Based on Dutch guidelines individuals aged ≥70 years were classified into 3 glycated haemoglobin (HbA1c) treatment target groups: 7% (53 mmol/mol), 7.5% (58 mmol/mol) and 8% (64 mmol/mol). In our cohort of 1002 patients (n = 319 aged ≥70 years), the 165 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 8 publications
(9 reference statements)
1
44
0
Order By: Relevance
“…The prevalence of polypharmacy regimen, defined as the use of more than 5 medications, increases with age. Results from a Dutch study revealed that 64 persons (20%) out of 319 type 2 diabetic patients aged ≥70 years were overtreated and frail (38). Furthermore, one-quarter of US older diabetic adults are on potential overtreatment for tight glycemic control using glucose-lowering medications at high risk of hypoglycemia (39).…”
Section: Diabetes and Geriatric Syndromesmentioning
confidence: 99%
“…The prevalence of polypharmacy regimen, defined as the use of more than 5 medications, increases with age. Results from a Dutch study revealed that 64 persons (20%) out of 319 type 2 diabetic patients aged ≥70 years were overtreated and frail (38). Furthermore, one-quarter of US older diabetic adults are on potential overtreatment for tight glycemic control using glucose-lowering medications at high risk of hypoglycemia (39).…”
Section: Diabetes and Geriatric Syndromesmentioning
confidence: 99%
“…28 In line with the concept of quaternary prevention-avoidance of overmedicalization in at-risk populations 29 , the definition of adequate glycaemic control should be revised in those vulnerable patients along with the promotion of the safest drugs, instead of insulin or SUs. Overtreatment in older diabetic patients is quite common and should be avoided in order to prevent harmful consequences such as falls resulting from hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Overtreatment in older diabetic patients is quite common and should be avoided in order to prevent harmful consequences such as falls resulting from hypoglycaemia. 28 In line with the concept of quaternary prevention-avoidance of overmedicalization in at-risk populations 29 , the definition of adequate glycaemic control should be revised in those vulnerable patients along with the promotion of the safest drugs, instead of insulin or SUs. In our study, we excluded patients with preintensification HbA1c values <7%, to minimize the possibility of overtreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Important points are avoiding overly intensive diabetes management and using therapies with a low risk of hypoglycaemia, as recommended by both the ADA and the Dutch College of General Practitioners [9, 20]. In clinical practise, de-intensifying glucose lowering treatment is not yet successfully implemented [21, 22].…”
Section: Discussionmentioning
confidence: 99%